Management of ischemic stroke in Central and Eastern Europe. (14th July 2015) - Budincevic, Hrvoje; Tiu, Cristina; Bereczki, Daniel; Kõrv, Janika; Tsiskaridze, Alexander; Niederkorn, Kurt; Czlonkowska, Anna; Demarin, Vida; ,
Abstract : Stroke is one of the leading causes of disability in Europe. Central and Eastern European countries have the highest incidence and mortality rates through Europe. The improvements in stroke prevention and treatment in Central and Eastern European countries did not completely reach the quality parameters present in Western European countries. We present features of current management of stroke in Central and Eastern European countries.